Kajian Model Pemberdayaan Ketahanan Pangan di Wilayah Perbatasan Antar Negara - Rizal Syarief; . Sumardjo; Anna Fatchiya (Institut Pertanian Bogor, 2014)
Malacca District is one of Indonesian border area with East Timor. This region is also become the home for largest number of refugees in East Timor after the poll.The existence of the East Timorese former warrior who lived in the ressetlement area built by the EU and UNHCR in Kanamasa village, Central Malaka subdistrict-Malacca District, need special attention amid uncertainty life after their struggle. The Central Malacca subdistrict classified as number one priority areas of food insecurity in East Nusa Tenggara according FSVA. The development of agriculture is alternative solutions in an effort to strengthen the refugees household food security. The purpose ofthis study wasto analyzethe condition of the availability of food, the factors causing food problems, and designing a model of community empowerment efforts to increase food security in the inter-state border. The results showed the condition of the people of East Timorex-fighters in a state of food insecurity that characterized the energy consumption below the cutting point for the adequacy of the energy consumption of 2.160Cal/cap/dayis equal to1209.08Cal/cap/day. Food problems that arise due to the lack of diversification factor, high food prices, and food cultureareless supportive of the adequacy of nutrient intake in the family. Agricultural development program is an effort to address the problem of food insecurity, with a capital in the community experience in agriculture. Programs that can be developed are: 1) institutional strengthening through the establishment of farmers' groups; 2) human resource development through training of crops and horticulture nursery; 3) optmize of yards land use; 4) initiation of land cultivation procurement; 5) agriculture activities in demonstration plots land.